2020
DOI: 10.1080/14760584.2020.1750378
|View full text |Cite
|
Sign up to set email alerts
|

Upper respiratory tract colonization withStreptococcus pneumoniaein adults

Abstract: Introduction: Most of the current evidence regarding pneumococcal upper respiratory colonization in adults suggests that despite high disease burden, carriage prevalence is low. Contemporary studies on adult pneumococcal colonization have largely followed the pediatric approach by which samples are obtained mostly from the nasopharynx and bacterial detection is evaluated by routine culture alone. Recent evidence suggests that the "pediatric approach" may be insufficient in adults and pneumococcal detection in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 128 publications
2
25
0
Order By: Relevance
“…The frequency [91] and density [43] of pneumococcal colonization are reported to be reduced in older adults, despite the incidence of pneumococcal CAP and IPD being highest in older age groups. However, recent studies appear to have resolved this seeming paradox, specifically by finding carriage prevalence of older adults approaching that in children when using molecular techniques and testing reservoirs other than the nasopharynx, such as the oropharynx and saliva [53,91,92]. Studies of experimental pneumococcal colonization indicate that colonization can be established in healthy older adults, but it failed to confer serotype-specific immunity [82].…”
Section: Age-related Defects In Innate Responsesmentioning
confidence: 99%
“…The frequency [91] and density [43] of pneumococcal colonization are reported to be reduced in older adults, despite the incidence of pneumococcal CAP and IPD being highest in older age groups. However, recent studies appear to have resolved this seeming paradox, specifically by finding carriage prevalence of older adults approaching that in children when using molecular techniques and testing reservoirs other than the nasopharynx, such as the oropharynx and saliva [53,91,92]. Studies of experimental pneumococcal colonization indicate that colonization can be established in healthy older adults, but it failed to confer serotype-specific immunity [82].…”
Section: Age-related Defects In Innate Responsesmentioning
confidence: 99%
“…Assays targeting the lytA and piaB genes were conducted as previously described ( 17 , 37 ). An assay for the GntR-type transcriptional regulator gene bguR ( 38 ) (TIGR4 NCBI reference sequence, NC_003028 ; locus tag, SP_RS10220; old locus tag, SP_2020), also referred to as SP2020 ( 19 , 29 ), used forward primer (5′-AGTTTGCCTGTAGTCGAATGA-3′), reverse primer (5′-TTTGAGCTGCCACGAGAG-3′) and the probe (5′-6-carboxyfluorescein [FAM]-AAACGTGGGCAGGGAACCTTTGTT-BHQ1-3′) concentrations of 300 nM, 100 nM, and 200 nM, respectively. No-template controls (blanks) were included in each qPCR run, and runs were balanced with approximately equal numbers of NP and OP samples.…”
Section: Methodsmentioning
confidence: 99%
“…Both studies concluded that sampling the oropharynx was superior to sampling the nasopharynx. A recent review examining studies of upper respiratory tract carriage of S. pneumoniae in adults, including those that utilized molecular methods, also encourages the sampling of other respiratory sites, such as OP and/or saliva, in addition to NP sampling ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Streptococcus pneumoniae (Spn) colonizes millions worldwide yearly, with a colonization prevalence particularly high in children and the elderly (1)(2)(3). In children, the prevalence of pneumococcal carriage can be as high as 90% in those from developing countries, or between 25-40% in children from industrialized nations (1,(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%